Syringe Access, Syringe Sharing, and Perceptions of HCV: A Qualitative Study Exploring the HCV Risk Environment in Rural Northern New England, United States - Eric Romo; Elyse Bianchet; Patrick Dowd; Kathleen M. Mazor; Thomas J. Stopka; Peter D. Friedmann (Viruses)
The ongoing hepatitis C virus (HCV) epidemic in the United States disproportionately affects rural people who inject drugs (PWID). This study explores the HCV risk environment in rural northern New England by examining PWID experiences and perceptions of HCV and injection equipment-sharing practices. We performed a thematic analysis on semi-structured interviews conducted with 21 adults with a history of injection drug use from rural New Hampshire, Vermont, and Massachusetts between April 2018 and August 2019. Salient themes included: (1) limited and varied access to sterile syringe sources; (2) syringe scarcity contributing to the use of informal syringe sources (e.g., secondary syringe exchange or syringe sellers who purchased syringes from out-of-state pharmacies); (3) syringe scarcity contributing to syringe sharing; (4) linkages among decisions about syringe sharing and perceptions of HCV risk, HCV status, and interpersonal trust; and (5) confusion and misconceptions about HCV, including difficulty learning one’s HCV status, inadequate HCV education, and misconceptions regarding HCV transmission and treatment. Efforts to prevent and eliminate HCV among rural PWID should expand syringe access, increase awareness of HCV as a serious but preventable risk, and acknowledge social connections as potential influences on syringe access and syringe-sharing decisions.